Orbital Compartment Syndrome Following Extracorporeal Support. Issue 5 (30th July 2013) - Brodt, Jessica; Gologorsky, Daniel; Walter, Scott; Pham, Si M.; Gologorsky, Edward
Abstract Orbital compartment syndrome (OCS) is a rare, catastrophic, but potentially treatable complication. It requires prompt diagnosis and immediate intervention, as critical period for possible functional recovery is very short. This report adds to our understanding of potential mechanisms of perioperative blindness, and suggests extracorporeal circulatory support, systemic inflammatory response, and massive blood and fluid resuscitation as potential risk factors for perioperative OCS. doi: 10.1111/jocs.12196 (J Card Surg 2013;28:522–524)